Estimating the cost of corrosion in Indian industry - Singh, Bineet; Basak, Munmun; West, Martin; Guha, Indranil (Petrotech, 2010)
Industries in India play an important role in the economic growth of country. These industries face challenging conditions in effective corrosion estimation, prevention and control. In today’s tough competition from fast growing China and other Asian countries, it has become necessary for the Indian industries to increase the production by minimizing the loss of shutdown and any accidents and at the same time optimal use of manpower and money. The cost of corrosion in chemical, manufacturing, transportation, oil and gas, petrochemical, refineries contribute an alarming proportion of the total cost of corrosion among all industries. This paper gives an overview of cost of corrosion in India and its relation with GDP. According to a recent report (NACE, India chapter) the corrosion cost in any developing country is predicted by 5% of the GDP. For India the cost of corrosion is estimated to be 36,000 Crores INR in 2008. This is about half of our defence budget and perhaps double of our total annual expenses on education. This is, therefore an enormous sum, which needs immediate attention and future strategy to minimize it and make our industry safer and accident-free. In this paper the forecasting methods were used to predict the corrosion cost for next 10 years for India. First the correlation between the corrosion cost, GDP and Index of Industrial Production (IIP) were established and then forecasting techniques were used to predict the future loss due to corrosion.